2018
DOI: 10.1021/acssuschemeng.7b03200
|View full text |Cite
|
Sign up to set email alerts
|

Regenerated Cellulose and Willow Lignin Blends as Potential Renewable Precursors for Carbon Fibers

Abstract: We report a method to extract lignin from willow, using triethyl ammonium hydrogen sulphate [Et3NH][HSO4. This method is used to manufacture fibers with a range of compositions.. This extraction achieved an 18% yield of lignin as characterized by ATR-IR and elemental analysis indicated a high carbon yield. 1-Ethyl-3-methylimidazolium acetate [C2C1im][OAc] was then used as a solvent to manufacture lignin-cellulose fiber blends. The Young's modulus of a 75:25 lignin:cellulose fiber was found to be 3.0 ±0.5 GPa w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 36 publications
4
37
1
1
Order By: Relevance
“…As a result, the composite fibres are now potential candidates for continuous CF production, rather than the less economical bath conversion process. As expected, the composite fibres had a higher carbon yield than traditional cellulose precursors, which is favourable for improved CF production (Olsson et al 2017;Vincent et al 2018;Bengtsson et al 2019). Olsson et al spun composite fibres from 70% kraft lignin and 30% cellulose as CF precursors using ionic liquid-based air gap spinning (Olsson et al 2017).…”
Section: Introductionsupporting
confidence: 66%
“…As a result, the composite fibres are now potential candidates for continuous CF production, rather than the less economical bath conversion process. As expected, the composite fibres had a higher carbon yield than traditional cellulose precursors, which is favourable for improved CF production (Olsson et al 2017;Vincent et al 2018;Bengtsson et al 2019). Olsson et al spun composite fibres from 70% kraft lignin and 30% cellulose as CF precursors using ionic liquid-based air gap spinning (Olsson et al 2017).…”
Section: Introductionsupporting
confidence: 66%
“…The I D / I G ratio is also in good agreement with other Raman measurements on lignin–cellulose-derived CFs. 15 According to the famous three-stage model for disordered carbons proposed by Ferrari and Robertson, an I D / I G of 0.9 suggests that amorphous carbon dominates the CF structure. 34 Conclusively, the results suggest that Raman spectroscopy is not capable of explaining the significant difference in Young’s modulus of the continuously derived CFs (46 GPa) and the batchwise derived CFs (63 GPa).…”
Section: Resultsmentioning
confidence: 99%
“…on the structure and mechanical properties of lignin/cellulose precursor fibers and carbon fibers have been investigated systematically [ 139 , 155 , 156 , 157 ], from which it is concluded that the cellulose constituent dominates precursor fiber structure and mechanical performance. Increasing lignin content decreases fiber strength due to the disturbance of oriented cellulose crystallites [ 141 , 158 , 159 ] and increases carbon yield [ 160 ] due to lignin’s carbon-rich structure. However, the draw ratio of solution-spun lignin/cellulose precursor fibers seemed to have no significant influence on the carbon fiber’s physical properties [ 155 ], although the detailed reasons from the perspective of fiber structure were not revealed.…”
Section: Mechanical Performance Of Lignin-based Fibersmentioning
confidence: 99%